New insights into the pathophysiology of post-stroke spasticity - Li, Sheng; Francisco, Gerard E. (Frontiers in Human Neuroscience, 2015)
Spasticity is one of many consequences after stroke. It is characterized by a velocity-dependent increase in resistance during passive stretch, resulting from hyperexcitability of the stretch reflex. The underlying mechanism of the hyperexcitable stretch reflex, however, remains poorly understood. Accumulated experimental evidence has supported supraspinal origins of spasticity, likely from an imbalance between descending inhibitory and facilitatory regulation of spinal stretch reflexes secondary to cortical disinhibition after stroke. The excitability of reticulospinal and vestibulospinal tracts has been assessed in stroke survivors with spasticity using non-invasive indirect measures. There are strong experimental findings that support the reticulospinal hyperexcitability as a prominent underlying mechanism of post-stroke spasticity. This mechanism can at least partly account for clinical features associated with spasticity and provide insightful guidance for clinical assessment and management of spasticity. However, the possible role of VST hyperexcitability can not be ruled out from indirect measures. In vivo measure of individual brainstem nuclei in stroke survivors with spasticity using advanced fMRI techniques in the future is probably able to provide direct evidence of pathogenesis of post-stroke spasticity.